Every fifteen minutes [compact disc, unabridged] - Scottoline, Lisa (Macmillan Audio, 2015)
Dr. Eric Parrish, a brilliant and caring psychiatrist, has been unknowingly targeted by a sociopath. His hands are already full, having recently separated from his wife and trying his best to be a single dad to his seven-year-old daughter. And now Eric faces a new challenge in the form of a troubled teenaged boy who harbors an obsessive crush on a girl. Because of secrets that this boy divulges in therapy, Eric grows concerned for the girl<U+2019>s safety and becomes embroiled in a dangerous dilemma: Should he report his potentially dangerous patient to the authorities? Just as Eric reaches his decision, the unimaginable happens. . .and the game is on. The clock begins ticking, and Eric finds himself plunged into a living nightmare<U+2015>and at the hands of a sociopath bent on destroying his practice, his family, and his life.